Measles in Chaopraya Yommaraj Hospital, Suphan Buri, Thailand (1998-2007) - Ratanapitchayachai, Pailin (Journal of Health Science of Thailand, 2017)
This long-term assessment of measles combined a prospective study of measles immunity in 90 children during measles outbreak at Chaoprayayommaraj Hospital from December 19, 1997 - June 29, 1998 and a retrospective review of measles cases from the fiscal year 1999 to 2007. In The first phase, the prospective study, using CDC criteria for clinical diagnosis, the patients obtained paired serum to determine measles antibody level by Micro-Neutralization and ELISA IgM technique. It was found that 50 percent of the patients were unvaccinated and 16 vaccinated patients (17.8%) still developed measles. Two of them were vaccinated while incubating natural measles and 14 patients (15.6%) were primary vaccine failure. Most of them recieved measles vaccine once at the age of 9 -12 months at small health centers. The epidemiologic study showed that 63.3 percent of the patients were in the 9 -15 years age group and 22.2 percent aged 4-9 years. The most common complications in this study were diarrhea and pneumonia. Only two acute encephalitis patients with complete recovery without permanent brain damage were found. In the second phase, the retrospective review of measles cases admitted in Chaoprayayommaraj hospital 1999-2007, after measles outbreak in 1998, reported a declining long-term trend of morbidity rate of measles. Exception was made in 2000 when increasing measles cases was found with 30.5 percent of the in-patients aged 1-4 years and 27.8 percent of the patients in each of the two age-groups of 9-15 years and 4-9 years. By recommendation of the extended program on immunization (EPI), Chaoprayayommaraj hospital has been giving the first dose of measles vaccine in nine- month old infants and the second dose at age of 4-6 years or the first grade of elementary school while an increasing of measles vaccine coverage of 99-100 percent in the province was reported. The success and impact of the effective vaccination program has been depicted as no outbreak of measles has been witnessed since 2000.